FLUKS BENTIK DAN POTENSI AKTIVITAS BAKTERI TERKAIT SIKLUS NITROGEN DI SEDIMEN PERAIRAN MANGROVE PULAU DUA, BANTEN - Iswantari, Aliati; Wardiatno, Yusli; Pratiwi, Niken T.M; Rusmana, Iman (Perhimpunan Biologi Indonesia, 2014)
Mangrove ecosystem has important role as source of nutrient particularly nitrogen in coastal area. Nitrogen (N) is alimiting factor in marine and coastal area. The aim of this research was to study benthic fluxes and potency ofbacterial activity in sediment of mangroves area, related to nitrogen cycle. This research was conducted in floodedmangroves area in Pulau Dua. The sediment and overlying water was sampled using sediment core sampler.Experimental treatment for flux analysis and sediment-slurry were conducted in three hours. Nutrient of NH3-N,NO2-N, and NO3-N and abundance of nitrifier, denitrifier, DNRA, and ammonifier were analyzed. The resultsshowed that the abundance of anaerobic bacteria was higher than aerobic bacteria. The dominance of bacterialgroups found in sediment was ammonification bacteria. The highest nutrient concentration in sediment was NH3-N. Benthic fluxes value showed higher NH3-N tends to release from the sediment to water than NO2-N and NO3-N. Generally, mangrove sediment in Pulau Dua has higher potency ofbacterial activity (Vmax and Km) in NO3reduction by anaerobic bacteria than NH3 oxidation by aerobic bacteria.Keywords: bacteria, benthic fluxes, mangrove, potency of bacterial activity, sediment